Estimation of self-incompatibility S genotypes of Citrus cultivars and plants based on controlled pollination with restricted number of pollen grains - Ngo, B.X., Kyushu Univ., Fukuoka (Japan); Wakana, A; Kim, J.H; Mori, T; Sakai, K (Journal of the Faculty of Agriculture, Kyushu University, 2010)
Self-incompatibility S genotypes of 29 Citrus cultivars were estimated by the observation of pollen tube behavior in the lower one-third of styles with the aid of an epifluorescent microscope 7 or 8 days after controlled pollination with restricted number of pollen grains (about 100) on their stigmas. In eight crosses considered to be fully compatible on the basis of segregation distortion of glutamate oxaloacetate transaminase (GOT) isozymes in the progenies of cultivars used for the crosses, the rate of pollen tubes reaching the style base ranged from 7.7% to 24.6% of pollen grains putting on the stigmas, while in twelve crosses considered to be semi-compatible the rate of pollen tubes reaching the style base ranged from 1.6% to 19.3% of pollen grains on the stigmas. The rates were slightly different in different pistillate parents. Twenty cultivars whose genotypes were not determined were pollinated with restricted number of 'Banpeiyu' (Ssub(1)Ssub(2)) pollen grains and their genotypes were predicted by the pollen tube behaviors. Similarly, 13 controlled crosses were carried out with restricted number of pollen grains and their S genotypes were determined based on the number of pollen tubes reaching the style base. From these results, it became clear that the predicted S genotypes of the cultivars are well correspond with pollen tube behaviors in full or semi compatible crosses and, eventually, it was estimated that 15 cultivars have either Ssub(1) or Ssub(2) allele that 'Banpeiyu' pummelo has.